An investigation into the feasibility of activity corridors as a solution to the spatial problems in Kuils River - Carelse, Ruby L.(Ruby Leoni) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1997.